Spatial and temporal distribution patterns of ichthyoplankton in a region affected by water regulation by dams - Tatiane M Gogola; Vanessa S Daga; Pedro R. L. da Silva; Paulo V Sanches; Éder A Gubiani; Gilmar Baumgartner; Rosilene L Delariva (Neotropical Ichthyology)
The aim of this work was to study the occurrence of ichthyoplankton in a region affected by water regulation by dams. The study area was located in the region of Ilha Grande National Park, upper Paraná River floodplain. Specifically, we examined the temporal and spatial distribution of Ichthyoplankton, identified spawning areas and established the relationships between the abundances of fish eggs and larvae and some limnological and hydrological variables. Samples were taken monthly between October and March from 2001 to 2005 at 24 sampling sites. For analytical purposes, the sampling sites were grouped into upper, middle and lower areas. The upper area of the National Park had the highest egg density and should be considered the primary spawning area. The middle area should be considered a drift area, and the lower area likely functions as a growth and feeding habitat. Statistical analyses showed that the spawning was influenced by water temperature, pH, fluviometric level and rainfall, and that larval density was influenced by pH, conductivity, dissolved oxygen and rainfall. The results also revealed that the tributaries apparently are used as migratory routes by fish, and and this shows the need to protect these sites.